2016
DOI: 10.1158/1078-0432.ccr-15-2335
|View full text |Cite
|
Sign up to set email alerts
|

Haploidentical versus Matched-Sibling Transplant in Adults with Philadelphia-Negative High-Risk Acute Lymphoblastic Leukemia: A Biologically Phase III Randomized Study

Abstract: Purpose: Although matched-sibling donor (MSD) hematopoietic stem-cell transplantation (HSCT) has an established role in the management of adults with acute lymphoblastic leukemia (ALL) in first complete remission (CR1), the effect of haploidentical donor (HID) HSCT as post-remission treatment for this portion of patients is not defined.Experimental Design: Transplantation outcomes from HIDs or MSDs were compared in a disease-specific, biologically phase III randomized, multicenter study. Between July 2010 and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
147
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 139 publications
(166 citation statements)
references
References 36 publications
(52 reference statements)
16
147
3
Order By: Relevance
“…Although the conditioning regimen for haplo-RD and URD HSCT was more intense than for ISD HSCT, several studies observed that the safety was similar in ISD and alternative donor HSCT recipients [7,19,20]. In addition, all the patients received sitz baths, had their perianal areas cleaned with 0.0005% iodophor solution after defecation, and received 2% iodoform-vaseline to protect the perianal skin.…”
Section: Discussionmentioning
confidence: 99%
“…Although the conditioning regimen for haplo-RD and URD HSCT was more intense than for ISD HSCT, several studies observed that the safety was similar in ISD and alternative donor HSCT recipients [7,19,20]. In addition, all the patients received sitz baths, had their perianal areas cleaned with 0.0005% iodophor solution after defecation, and received 2% iodoform-vaseline to protect the perianal skin.…”
Section: Discussionmentioning
confidence: 99%
“…66,[79][80][81][82][83][84][85][86] Therefore, lack of an HLA-matched donor does not preclude favorable transplantation outcomes. …”
Section: Discussionmentioning
confidence: 99%
“…85 A randomized, multicenter study in 210 patients with Philadelphia-negative ALL in CR1 showed 3-year disease-survival was ;65% after matched sibling and haploidentical transplantation. 86 Albeit nonrandomized, these studies suggest equivalence of haploidentical transplantation with matched sibling and unrelated donor transplantation.…”
Section: Haploidentical Vs Matched Hematopoietic Transplantationmentioning
confidence: 95%
“…7-10 However, current clinical practice is supported by the results of HID HCT and clinical trials organized by Huang et al (some trials are listed in Table 1). [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] The AML patient subgroup classified in the low-risk karyotype by the World Health Organization stratification system, obtained benefit from allogeneic HCT in CR1 status following re-stratification by applying risk-directed therapy based on MRD. In a trial registered at http://www.chictr.org.cn/enIndex.aspx as #ChiCTR-OCH-12002406, 13 the high-risk group was defined as those patients not achieving major molecular remission (MMR) after the second consolidation therapy or those exhibiting the loss of MMR within 6 months of achieving MMR.…”
Section: Allogeneic Hct Trendsmentioning
confidence: 99%